Which ICU patients benefit most from inspiratory muscle training? Retrospective analysis of a randomized trial. (1st December 2020) - Bissett, Bernie M; Wang, Jiali; Neeman, Teresa; Leditschke, I Anne; Boots, Robert; Paratz, Jennifer
ABSTRACT: Background : Inspiratory muscle training (IMT) increases inspiratory muscle strength and improves quality of life in intensive care unit (ICU) patients who have been invasively mechanically ventilated for ≥7 days. The purpose of this study was to identify which patients benefit most from IMT following weaning from mechanical ventilation. Methods : Secondary analysis of a randomized trial of supervised daily IMT in 70 patients (mean age 59 years) in a 31-bed ICU was carried out. Changes in inspiratory muscle strength (maximum inspiratory pressure, MIP) between enrolment and 2 weeks (ΔMIP) were analyzed to compare the IMT group (71% male) and the control group (58% male). Linear regression models explored which factors at baseline were associated with ΔMIP. Results : Thirty-four participants were allocated to the IMT group where baseline MIP was associated with an increase in ΔMIP, significantly different from the control group ( p = 0.025). The highest ΔMIP was associated with baseline MIP ≥ 28 cmH2 O. In the IMT group, higher baseline quality of life (EQ5D) scores were associated with positive ΔMIP, significantly different from the control group ( p = 0.029), with largest ΔMIP for those with EQ5D ≥ 40. Conclusions : Physiotherapists should target ICU patients with moderate inspiratory muscle weakness (MIP ≥28 cmH2 O) and moderate to high quality of life (EQ5D>40) within 48 h of ventilatory weaning as ideal candidates for IMT following prolonged mechanical ventilation.